The experience and meaning of family in youth-headed households from Gauteng, Katlehong Township - Molemane, Sibongile Petronella (My University, 2022)
South Africa is considered to be a developing country and as the country evolves, various societal issues become evident, posing various challenges to communities in the country. Therefore, as the country tries to deal with these societal issues, communities and its people are forced to make changes as they try to adapt to the shifting norms. The family system and its structures seem to highlight some of the changes, with child and youth-headed households becoming more prevalent and a norm in South African communities. This research study is aimed at exploring how individuals heading youth-headed households experience their roles and responsibilities as heads, and the challenges they have experienced in maintaining their family units. Furthermore, this study aims to understand what the concept of family means to these young people, as their family system is different to the norm and what support they have received while heading their families. A qualitative research approach, specifically phenomenological research design was used in this study. Five participants (3 females and 2 males) aged between 19-35 years, from Katlehong, a township in Gauteng were purposively selected and requested to participate in the study. Data was collected through individual semistructured interviews and data was analysed using Interpretative Phenomenological Analysis (IPA). Six main themes emerged from the findings of the study, with findings suggesting that participants became the heads of their household/families following the death of parents/caregivers and feeling abandoned by some of their extended family members. Participants reflected on some of the responsibilities they have and the sacrifices they have made in order to sustain their households. Findings further highlighted the state of poverty that exists in these households and the lack of efficient support from the governmental social systems, with participants having to rely on the support and assistance of community members or an NGO
A research report submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in partial fulfilment for the degree of MA by Coursework and Research Report, in the field of Clinical Psychology, 2021.